Unique and contrasting structures of homoleptic lanthanum(iii) and cerium(iii) 3, 5-dimethylpyrazolates. Issue 17 (16th April 2018) - Werner, Daniel; Bayer, Uwe; Rad, Nazli E.; Junk, Peter C.; Deacon, Glen B.; Anwander, Reiner
Abstract : Six coordination modes are observed in the tetranuclear cage [Ce4 (Me2 pz)12 ] while lanthanum features a coordination polymer with an unusual η 5 :η 5 Me2 pz sandwich. Abstract : Homoleptic [La(Me2 pz)3 ] n (Me2 pz = 3, 5-dimethylpyrazolato) is a μ–η 2 :η 5 -Me2 pz coordination polymer with 12-coordinate La atoms in an unusual η 5 :η 5 Me2 pz sandwich, whilst the cerium congener forms a molecular tetrametallic cage [Ce4 (Me2 pz)12 ] featuring six different Me2 pz coordination modes.